MENJAGA WARISAN LELUHUR: Tradisi dan Nilai Islam dalam Budidaya Pala di Kepulauan Banda - Tora, Rusdan La (BANDA HISTORIA: Jurnal Pendidikan Sejarah dan Studi Budaya, 2025)
This study aims to examine the practice of nutmeg (Myristica fragrans) cultivation in the Banda Islands and identify the integration of Islamic values in these activities as part of local cultural heritage. This study is based on the importance of preserving agricultural traditions that are rich in religious and social values amidst the pressures of modernization and globalization. A qualitative approach with ethnographic methods was used to gain an in-depth understanding through participatory observation, in-depth interviews, and document studies involving farmers, traditional leaders, and religious leaders in Banda District, Central Maluku Regency. The results of the study indicate that the tradition of nutmeg cultivation in Banda not only functions as an economic activity but also becomes a manifestation of the practice of Islamic values such as tawakkul (surrender to Allah), patience, gratitude cooperation, and responsibility. These agricultural practices are passed down from generation to generation and integrated with local wisdom such as pela and gandong, which are in line with Islamic principles of ukhuwah (brotherhood) and tasamuh (tolerance).